Application of Health Knowledge in Dairy Cows at Pamegatan Village Cikajang Sub-district Garut District West Java Province - Raden Febrianto Christi; U Hidayat Tanuwiria; Primiani Edianingsih (UNIVERSITAS KHAIRUN, 2020)
An indicator of the success of a livestock business is maintenance management carried out by farmers or people as managers. The health factor is a guarantee that must be considered because it is very influential on livestock productivity. This community service activity is carried out with the aim of increasing the knowledge of dairy farmers in the field of animal health so that they are able to analyze properly. Community service was attended by 30 dairy farmers located in Pamegatan Village, Cikajang Subdistrict, Garut Regency through the stages of activities carried out including material socialization (Focus Group Discussion), training, mentoring and evaluation. The results of this service activity can increase the knowledge and applicability of farmers in response to animal health. Dairy cows consisting of calves, young cows, and adults have different health practices to support their productivity so that the breeders can understand about conditions such as what diseases each attack. Therefore, it is expected to be given this counseling on the health of dairy farmers to understand all types of diseases as well as prevention or its applicative efforts.Keywords: Health application, dairy cows, breeder groups, Cikajang-Garut